POPDC2 a novel susceptibility gene for conduction disorders. (August 2020) - Rinné, Susanne; Ortiz-Bonnin, Beatriz; Stallmeyer, Birgit; Kiper, Aytug K.; Fortmüller, Lisa; Schindler, Roland F.R.; Herbort-Brand, Ursula; Kabir, Nashitha S.; Dittmann, Sven; Friedrich, Corinna; Zumhagen, Sven; Gualandi, Francesca; et al.
Abstract: Despite recent progress in the understanding of cardiac ion channel function and its role in inherited forms of ventricular arrhythmias, the molecular basis of cardiac conduction disorders often remains unresolved. We aimed to elucidate the genetic background of familial atrioventricular block (AVB) using a whole exome sequencing (WES) approach. In monozygotic twins with a third-degree AVB and in another, unrelated family with first-degree AVB, we identified a heterozygous nonsense mutation in the POPDC2 gene causing a premature stop at position 188 (POPDC2 W188⁎ ), deleting parts of its cAMP binding-domain. Popeye-domain containing (POPDC) proteins are predominantly expressed in the skeletal muscle and the heart, with particularly high expression of POPDC2 in the sinoatrial node of the mouse. We now show by quantitative PCR experiments that in the human heart the POPDC-modulated two-pore domain potassium (K2P ) channel TREK-1 is preferentially expressed in the atrioventricular node. Co-expression studies in Xenopus oocytes revealed that POPDC2 W188⁎ causes a loss-of-function with impaired TREK-1 modulation. Consistent with the high expression level of POPDC2 in the murine sinoatrial node, POPDC2 W188⁎ knock-in mice displayed stress-induced sinus bradycardia and pauses, a phenotype that was previously also reported for POPDC2 and TREK-1 knock-out mice. We propose that the POPDC2 W188⁎ loss-of-function mutation contributes to AVB pathogenesis by an aberrant modulation of TREK-1, highlighting that POPDC2 represents a novel arrhythmia gene for cardiac conduction disorders.